Language learning strategies : a narrative literature review - Koondbar, Mansoor; M. Anthony, Elizabeth (Penerbit UTHM, 2020)
Language Learning Strategies (LLS) are the steps or actions that a learner consciously takes to improve and regulate his or her language learning (Cohen & Macaro, 2009; Griffiths, 2013; Oxford, 2011). This chapter focuses on a narrative review of the use and effectiveness of LLS in second language learning (L2) contexts. This investigation provides teachers and researchers with a thorough understanding of LLS besides highlighting research gaps.